" Ulama" and politics in Saudi Arabia - Layish, Aharon (Islam and politics in the modern Middle East, 1984)
The author shows how a puritanical religious renaissance movement, the Wahhabiyya, led to the most theocratic state in the Sunni Muslim world, and how the "ulama" still control the judicial system in Saudi Arabia. He describes how the status of the "ulama" has gradually declined, and how they have become aware of the political and military considerations that guide the ruler. The Saudi kings, on the other hand, have continued to deliberately resort to traditional legitimation. He also points out that, traditional legitimation notwithstanding, the shari'a laws have been reformed along mainly utilitarian lines, and that completely secular subjects have been introduced in the universities. One may thus surmise that "the most theocratic state" is now not at all that theocratic. (DÜI-Asd)